An innovative high energy efficiency–based process enhancement of hydrogen liquefaction: Energy, exergy, and economic perspectives. (15th July 2022) - Lee, Hyunhee; Haider, Junaid; Abdul Qyyum, Muhammad; Choe, Changgwon; Lim, Hankwon
Graphical abstract: Highlights: Precooling is an energy–intensive section due to large temperature difference. Process enhancement using two precooling cycles with addition of HFO in 1st cycle. Energy consumption of precooling section reduced from 4.197 to 2.83 kWh/kgLH2 . Specific energy consumption of process is 4.55 kWh/kgLH2 with 67% exergy efficiency. Annual cost of proposed process is $1.89 × 10 6 /y and $5.18/kg LH2 at 1TPD. Abstract: Hydrogen liquefaction can be one of the effective and viable solutions to enhance its energy contents for storage and transportation purposes. However, liquefaction of H2 is highly energy intensive where precooling is the most significant energy consumption section (∼50% of overall process) due to huge reduction in temperature (25 to −159.4 °C). In this context, in proposed study the precooling cycle is split into two cycles for reducing the energy consumption, 1) Hydrofluoroolefin–based mixed refrigerant stream which reduces the H2 temperature to −30 °C and 2) Mixed refrigerant stream which tends to reduce the H2 temperature up to −159.4 °C. This is the first study which utilizes the four refrigeration cycles with unique selection of HFO–based mixed refrigerants in precooling section to reduce the gaseous H2 temperature. Results of proposed study reveal that the specific energy consumption of proposed process was reduced by 55.2 % and 29.5%, as compared to base case–I (10.15 kWh/kgLH2 ) and base case–II (6.45 kWh/kgLH2 ), respectively. The exergy efficiency of the proposed process was increased by 67%. In addition, results of economic evaluation depicted that the total annualized cost of proposed process was obtained as $1.89 × 10 6 /y where the CAPEX has share of ∼ 71.7% in total cost of project. The estimated unit production cost was recorded as $5.18/kg of LH2 at the capacity of 1TPD. The simplicity and less energy consumption of proposed model built a basis for its development to commercial scale adoption.